20p-(7+2p)=

Simple and best practice solution for 20p-(7+2p)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20p-(7+2p)= equation:


Simplifying
20p + -1(7 + 2p) = 0
20p + (7 * -1 + 2p * -1) = 0
20p + (-7 + -2p) = 0

Reorder the terms:
-7 + 20p + -2p = 0

Combine like terms: 20p + -2p = 18p
-7 + 18p = 0

Solving
-7 + 18p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 18p = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 18p = 0 + 7
18p = 0 + 7

Combine like terms: 0 + 7 = 7
18p = 7

Divide each side by '18'.
p = 0.3888888889

Simplifying
p = 0.3888888889

See similar equations:

| z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 | | 5+2y=(-1) | | -14x+2y=-2 | | -3(2a-3)=3(a-6) | | h+4=2h-19 | | z=3*x-y | | y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) | | 4x+3=2(2x+2)-2x | | y=0.75(4)x | | 4=-0.5x^2+46 | | 42=12+3p | | 31(2c+4)=2(c+6)+c | | 7[2e-1]-3=6+6e | | 32=7(n+7)+5(5n+3) | | Y+2=.6(x+4) | | 42=2.333333x | | 6x+34x=7 | | 10p-3=2[12+4p]-7 | | 800=2x+3x+10x | | 9g=3[-4+5g] | | 500=2x+8x | | Y=-.6x-1 |

Equations solver categories